Estimating the Effects of Global Patent Protection in Pharmaceuticals: A Case Study of Quinolones in India - Chaudhuri, Shubham; Goldberg, Pinelopi K; Jia, Panle (American Economic Review, 2006)
Under the Agreement on Trade-Related Intellectual Property Rights, the World Trade Organization members are required to enforce product patents for pharmaceuticals. In this paper we empirically investigate the welfare effects of this requirement on developing countries using data for the fluoroquinolones subsegment of the systemic anti-bacterials segment of the Indian pharmaceuticals market. Our results suggest that concerns about the potential adverse welfare effects of TRIPS may have some basis. We estimate that the withdrawal of all domestic products in this subsegment is associated with substantial welfare losses to the Indian economy, even in the presence of price regulation. The overwhelming portion of this welfare loss derives from the loss of consumer welfare.